PENGEMBANGAN NUGGET OLAHAN TEPUNG TULANG IKAN TUNA (Thunnus sp) DAN ANALISIS KANDUNGAN KALSIUM - Ameylia Nur Anggraini; Kurnia Mar'atus Solichah; Diah Puspitasari (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
A Calcium is an important macromineral that plays a role in bone and tooth formation and helps maintain bone density. Calcium deficiency can increase the risk of osteoporosis. Tuna bone meal is a fairly high source of calcium that can be used as an ingredient in food products such as nuggets. The objective of this study is to help identify and develop alternative calcium sources that can be used in functional food products, such as tuna fish bone flour (Thunnus sp), which has the potential to increase calcium intake in the community. This study used a non-factorial Complete Randomized Design (CRD) consisting of three treatments: P1 (30% tuna fish bone flour), P2 (40% tuna fish bone flour), and P3 (50% tuna fish bone flour). Hedonic testing was conducted on the attributes of color, aroma, taste, texture, and overall quality using a scale of 1–5 by 33 moderately trained panelists. Calcium content analysis in the nuggets was performed using the Atomic Absorption Spectrophotometry (AAS) method. Statistical analysis used the Kruskal-Wallis test and the Mann-Whitney test. The preference test results showed no significant differences in color (p=0.251), aroma (p=0.308), and texture (p=0.643), while there were significant differences in taste (p=0.036) and overall quality (p=0.038). The preference test results showed that panelists preferred formulation P1 in terms of color, aroma, taste, and overall quality, making P1 the best formulation with a calcium content of 3.29%. One serving of tuna fish bone flour nuggets (40g) can meet ±100% of the daily calcium requirement.